Drivers of the relative richness of naturalized and invasive plant species on Earth. Issue 5 (4th September 2019) - Essl, Franz; Dawson, Wayne; Kreft, Holger; Pergl, Jan; Pyšek, Petr; Van Kleunen, Mark; Weigelt, Patrick; Mang, Thomas; Dullinger, Stefan; Lenzner, Bernd; Moser, Dietmar; Maurel, Noëlie; et al.
Abstract: Biological invasions are a defining feature of the Anthropocene, but the factors that determine the spatially uneven distribution of alien plant species are still poorly understood. Here, we present the first global analysis of the effects of biogeographic factors, the physical environment and socio-economy on the richness of naturalized and invasive alien plants. We used generalized linear mixed-effects models and variation partitioning to disentangle the relative importance of individual factors, and, more broadly, of biogeography, physical environment and socio-economy. As measures of the magnitude of permanent anthropogenic additions to the regional species pool and of species with negative environmental impacts, we calculated the relative richness of naturalized (= RRN) and invasive (= RRI) alien plant species numbers adjusted for the number of native species in 838 terrestrial regions. Socio-economic factors (per-capita gross domestic product (GDP), population density, proportion of agricultural land) were more important in explaining RRI (~50 % of the explained variation) than RRN (~40 %). Warm-temperate and (sub)tropical regions have higher RRN than tropical or cooler regions. We found that socio-economic pressures are more relevant for invasive than for naturalized species richness. The expectation that the southern hemisphere is more invaded than the northern hemisphere was confirmed only for RRN on islands, but not for mainland regions nor for RRI. On average, islands have ~6-fold RRN, and >3-fold RRI compared to mainland regions. Eighty-two islands (=26 % of all islands) harbour more naturalized alien than native plants. Our findings challenge the widely held expectation that socio-economic pressures are more relevant for plant naturalization than for invasive plants. To meet international biodiversity targets and halt the detrimental consequences of plant invasions, it is essential to disrupt the connection between socio-economic development and plant invasions by improving pathway management, early detection and rapid response. Abstract : The human-mediated introduction of species outside their native range is considered to be one of the greatest threats to biodiversity, yet a comprehensive analysis of the drivers of global invasions is currently lacking. Here, we use a novel database of naturalized and invasive plant species richness to analyse the effects of biogeographical, physical environment and socio-economic factors on the numbers of naturalized and invasive plant species relative to native species in 838 terrestrial regions. We demonstrate that the numbers of naturalized and invasive plant species relative to native species richness is highest on (sub)tropical islands, and that socio-economic factors foster invasive spread after naturalization. To meet international biodiversity targets and to halt the detrimental consequences of plant invasions, it is essential to disrupt the connection between socio-economic development and rising levels of plant invasions by improving pathway management, early detection and rapid response.